Control of solid oxide fuel cells damage using infrared thermography. (14th April 2020) - El-amiri, Asseya; Saifi, Abderrahim; Elhassnaoui, Ahmed; Obbadi, Abdellatif; Errami, Youssef; Sahnoun, Smail
Abstract: The high operating temperature of solid oxide fuel cells, can cause serious damage such as cathode delamination or cracking of the SOFC layers, which cause a decrease in the performance of the latter, a rigorous nondestructive inspection is necessary, in particular that their prices are high. In this paper we have treated thermal control by pulsed infrared thermography of the solid oxide fuel cells electrodes, using 3D finite elements method. The thermal images obtained were processed, and a quantitative analysis was performed to obtain information concerning cracks in electrolyte supported and anode supported planar cells, and cathode delamination in electrolyte supported and cathode supported cells. The results obtained as the temperature distribution in the fuel cells, with and without defects, shows the difference between the flawed and the unflawed cells. The thermal response informs us about the presence of the defects, and in addition it informed us about their depths. Highlights: The pulsed infrared thermography technique was applied to the oxide fuel cells damages detection. The technique is based on an instantaneous pulse light excitation. The results obtained in term of damages detection show the effectiveness of the technique used.